Pengaruh Kemasan dan Inovasi Produk terhadap Keputusan Pembelian Water Base Ink Pada Industri Percetakan Fleksibel Packaging di PT Samudera Warna Internasional - Abigail Lituhayu; Sanita Dhakirah; Lina Budiarti (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effect of product packaging and product innovation on purchasing decisions for water-based ink in the flexible packaging industry at PT Samudera Warna Internasional. The research is motivated by the gap between the high market potential for eco-friendly inks and the company's fluctuating sales realization. This quantitative study utilizes an explanatory research method. The sample consisted of 60 active consumer companies drawn from a population of 150 companies (January–March 2026 period) using a simple random sampling technique (10% margin of error). Data were collected through Likert-scale questionnaires, observation, and documentation. The data analysis included instrument feasibility tests, classical assumption tests, multiple linear regression, and hypothesis testing (t-test and F-test). The results prove that, both partially and simultaneously, product packaging and product innovation have a positive and significant effect on purchasing decisions. Specific findings indicate that product packaging has a more dominant influence than product innovation. In conclusion, consumer purchasing decisions heavily depend on the quality of visual communication through packaging and the adaptability of product innovation. Therefore, the company is advised to continuously improve packaging design to be more informative and consistently conduct Research and Development (R&D). This research provides a theoretical contribution to marketing management literature regarding consumer behavior toward eco-friendly industrial products.